Strategic priorities for the development of the halal industry in the region: a case study of Bangkalan Regency - Isdiana Suprapti; Ririn Kusmawati; Nurul Arifiyanti; Resti Prastika Destiarni (Agriekonomika, 2025)
Bangkalan Regency has the potential to develop the halal industry, supported by a predominantly Muslim population and the growth of MSMEs in the processing sector. However, there has not yet been a mapping of priority areas and flagship commodities that can serve as the basis for formulating a local-based halal industry development strategy. This study aims to determine the strategic priorities for regional halal industry development in Bangkalan Regency. The Analytical Hierarchy Process (AHP) approach was used, involving 17 stakeholders from local government agencies and halal certification support institutions to evaluate five main criteria: human resources, policy support, infrastructure, partnerships, and raw material potential. The analysis results show that human resources are the most dominant factor in determining development priorities, followed by policy support and infrastructure. At the regional level, the districts of Bangkalan, Socah, and Arosbaya are identified as the main priorities based on production capacity and local resource support. These findings emphasize that region-based halal industry development strategies need to prioritize human resource readiness and access to certification as key factors in regional planning.